2021
DOI: 10.1186/s12978-021-01102-1
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among outpatient reproductive health care providers during the US COVID-19 epidemic

Abstract: Introduction Both inpatient and outpatient providers may be at increased risk of stress, anxiety and depression from their roles as health providers during the COVID-19 epidemic. This study explores how the US COVID-19 epidemic has increased feelings of stress, anxiety and depression among outpatient reproductive health providers. Methods We conducted a survey with open-ended responses among outpatient reproductive health providers across the U.S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
12
1
6
Order By: Relevance
“…Stress can lead to feelings of anxiety, fear, guilt, anger, social withdrawal, rumination, depression, insomnia and negative self‐assessments (Karnatovskaia et al., 2020). Since the onset of the pandemic, healthcare workers have experienced worsening work conditions and increased workloads; understaffing; faulty or missing personal protection and other medical equipment; a lack of testing; unmet needs for training, such as respiratory training for patients with COVID‐19; and higher than usual rates of sickness and death due to complications related to COVID‐19 among patients and colleagues (Chirico et al., 2021; Comfort et al., 2021; Norful et al., 2021; Walker & Tolentino, 2020).…”
mentioning
confidence: 99%
“…Stress can lead to feelings of anxiety, fear, guilt, anger, social withdrawal, rumination, depression, insomnia and negative self‐assessments (Karnatovskaia et al., 2020). Since the onset of the pandemic, healthcare workers have experienced worsening work conditions and increased workloads; understaffing; faulty or missing personal protection and other medical equipment; a lack of testing; unmet needs for training, such as respiratory training for patients with COVID‐19; and higher than usual rates of sickness and death due to complications related to COVID‐19 among patients and colleagues (Chirico et al., 2021; Comfort et al., 2021; Norful et al., 2021; Walker & Tolentino, 2020).…”
mentioning
confidence: 99%
“…The authors also reported that the most common coping behavior was physical therapy or exercise, while most responders were interested in an individual therapist with online self-guided counseling. Comfort et al ( 30 ) conducted a study on HCWs from an outpatient clinic in April–June 2020 and assessed their mental health challenges during the COVID-19 pandemic. The authors found that there was a two-third increase in stress levels, whereas there was a one-third increase in anxiety/depression levels.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons were mostly due to patient care, worrying about contracting and spreading infection, work- and home-related concerns, burnout, and fear of the unknown. Other contributory factors were lack of personal protective equipment, difficulty coping with co-worker illness, and absence ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of studies (Comfort et al, 2021;Havaei et al, 2021;Smith et al, 2020) and surveys (Registered Practical Nurses Association of Ontario, 2021; Statistics Canada, 2021) carried out in North America have indicated also that the health of HCWs, including nurses, was weakened. In a cross-sectional correlational study conducted in British Columbia, Canada, Havaei et al (2021) examined the impact of COVID-19 workplace conditions on mental health outcomes in a sample of 3,676 nurses and found the following prevalence rates: post-traumatic stress disorder 47%, anxiety 38%, depression 41% and high emotional exhaustion 60%.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The results of studies (Comfort et al., 2021; Havaei et al., 2021; Smith et al., 2020) and surveys (Registered Practical Nurses Association of Ontario, 2021; Statistics Canada, 2021) carried out in North America have indicated also that the health of HCWs, including nurses, was weakened. In a cross‐sectional correlational study conducted in British Columbia, Canada, Havaei et al.…”
Section: Introductionmentioning
confidence: 99%